COVID-19: Engaging the Most Vulnerable - Babacan, Hurriyet; Gopalkrishnan, Narayan (ASEAN Journal of Community Engagement, 2021)
The COVID-19 pandemic has had large-scale global effects across all segments of society, affecting large and diverse population cohorts in many ways. COVID-19 is not just a global health emergency but also a health-driven socioeconomic disaster. The prevalence of socioeconomic stressors that existed prior to the pandemic is exacerbated by the effects of the pandemic. The effects of COVID-19 vary across communities and are disproportionate on vulnerable groups. People with the least resources are most affected and are least able to recover. Contemporary thinking on development focuses on “bottom-up” approaches and “top-down” critique development. A key dimension of inclusiveness is about giving voice and power to excluded and vulnerable groups in development and recovery processes. Participation is a key ingredient in inclusive forms of development; it enables voice, representation, and capacity building to allow communities to address key societal challenges in line with their aspirations. This chapter argues that wide-scale community involvement is required for a sustainable recovery and resilience from COVID-19. It explores the benefits of participation in building long-term resilience and adaptive capacity. Participation is identified as a mechanism to enable ways to address power relations for vulnerable groups in COVID-19 recovery and curb the further deepening of global inequality.